ANALISIS USABILITAS WEBSITE SIAM UMRI MENGGUNAKAN METODE USABILITY TESTING - Faradila Ananda Yul; Miftahul Jannah (Jurnal Surya Teknika, 2020)
The thing that underlies the existence of a website is the development of information and communication technology. This study aims to measure the Usability level of the Student Academic Information System (SIAM) Website at Universitas Muhammadiyah Riau. Some problems encountered were that there was no reusability evaluation of the UMRI SIAM website, as well as complaints from UMRI students when accessing the website. The reusability problem in this study was resolved by conducting usability testing with five dimensions proposed by Nielsen (1993), namely learnability, efficiency, memorability, error & user satisfaction when accessing the SIAM UMRI website and using the thinking aloud method which required 3-5 respondents. The subjects studied were expert users (UMRI students) and novice users (non-UMRI students). Based on the results of the analysis on the learnability dimension, it is found that the respondents have the ability to learn a good website. In the efficiency dimension, the results of the increase in the speed of completing tasks by the respondents are obtained. Furthermore, in the memorability dimension, the results show that the respondents have good memory ability. In the error dimension, there are 38 problems when accessing the SIAM UMRI website, and in the satisfaction dimension, the results of respondents' satisfaction when accessing the SIAM UMRI website are obtained with a score of 70. In addition, in this study there are recommendations for improving the SIAM UMRI website.